Mummified Thyroid Nodules: Conventional and Contrast‐Enhanced Ultrasound Features. (12th August 2018) - Peng, Qinghai; Niu, Chengcheng; Zhang, Qianrong; Zhang, Meixiang; Chen, Sijie; Peng, Qiang
Abstract : Objectives: The purpose of our study was to highlight the conventional and contrast‐enhanced ultrasound (US) features of mummified thyroid nodules, which should help differentiate them from histologically proven papillary thyroid carcinomas (PTCs). Methods: Thirty‐one patients with 33 mummified thyroid nodules, which showed suspicious US findings that were suggestive of malignancy, as well as 33 patients with 38 surgically confirmed PTCs were enrolled in this study. We evaluated the size, shape, margin, echogenicity, presence of shadowing and halo, presence of punctate echogenic foci, vascularity, and contrast enhancement parameters for each nodule. The final diagnosis of mummified thyroid nodules was confirmed via fine‐needle aspiration (FNA) or surgery. Results: Of the 33 mummified thyroid nodules, 9 (27.3%) were confirmed by surgery to be benign, and 24 (72.7%) were proven by FNA to be benign. A univariate analysis indicated that the mummified thyroid nodules more frequently showed wider‐than‐tall shapes, marked hypoechogenicity, the presence of posterior shadowing, the absence of nodular vascularity, hypoenhancement or no enhancement, and peak index and area under the curve indices of less than 1 in the findings of preoperative US and contrast‐enhanced US compared to PTCs. A multivariate analysis showed that marked hypoechogenicity and an area under the curve index of less than 1 were independent characteristics related to mummified nodules for discriminating from PTCs (all P  < .05). Conclusions: Benign thyroid nodules may display shrinkage over time and may reveal malignant US features. Awareness of these findings and their connection with initial and follow‐up US examinations should help identify mummified thyroid nodules and to avoid surgical excision or unnecessary FNA.